Experimental and analytical analysis of aerodynamic lift of an ornithopter at low and high angles of attack. (May 2019) - Bakhtiari, Abdolbaghi; Etemadi Haghighi, Shahram; Maghsoudpour, Adel
In this study, a model based on potential flow theory is developed to analyze the unsteady nonlinear aerodynamics of a flexible flapping wing at low and high angles of attack. It is assumed that the wing motion is composed of twisting and flapping. The developed unsteady two-dimensional model is applied to the flapping wing using a blade-element-type method. The computational model presented in this study shows better agreement with experimental data especially at a high angle of attack. Analytical results also show that the wings section does not necessarily twist linearly along the wingspan.